A Review on Adolescent Sleep Deprivation and its Correlation with Hypertension: Review Article (Journal of Pharma Insights and Research, 2025)
Sleep deprivation poses a significant health challenge among adolescents, with mounting evidence linking insufficient sleep to increased risk of hypertension. Adolescence represents a critical period of physiological and behavioral changes, during which sleep patterns undergo substantial modifications due to biological, social, and environmental factors. The relationship between sleep deprivation and hypertension in teenagers involves complex physiological mechanisms, including sympathetic nervous system activation, endothelial dysfunction, and hormonal imbalances. Recent epidemiological studies indicate that approximately 73% of high school students report insufficient sleep, while the prevalence of hypertension among adolescents ranges from 4-7.6% globally. Sleep disorders, particularly obstructive sleep apnea and insomnia, further compound the risk of developing hypertension in this age group. Lifestyle factors, including dietary habits, physical activity levels, and screen time exposure, significantly influence both sleep quality and blood pressure regulation. Therapeutic interventions include cognitive behavioral therapy, chronobiological interventions, and lifestyle modifications. Despite growing research in this field, significant gaps remain in our knowledge of the causal relationships and long-term cardiovascular implications. The aim of this paper was to study current evidence on the bidirectional relationship between sleep deprivation and hypertension in adolescents, that can help in preventive and therapeutic interventions